Evaluation of ten tropical legume forages for their potential as pig feed supplement - Heinritz, S.N.; Hoedtke, Sandra; Martens, S.; Peters, Michael; Zeyner, Annette (2012)
Herbage of Cratylia argentea, Desmodium velutinum, Fleminigia macrophylla, Leucaena diversifolia, Canavalia brasiliensis, Centrosema brasilianum, Clitoria ternatea, Lablab purpureus, Stylosanthes guianensis and Vigna unguiculata from the CIAT (International Center for Tropical Agriculture) gene bank were assessed for their nutritional value and in-vitro digestibility for pigs in order to predict their potential as alternative protein supplement in a tropical smallholder context. Crude protein (CP) contents ranged from 137 to 257 g kg-1 dry matter (DM) (mean 191 g kg-1 DM), although a considerable proportion of it, 27 % on average, was bound to neutral detergent fiber (NDF). Interesting levels of lysine were found in Cratylia argentea (14 g kg-1 DM) and Leucaena diversifolia (13 g kg-1 DM), whereby the latter was also high in tannic acid concentration (49 g kg-1 DM) thus limiting the amino acid digestibility. Vigna unguiculatapresented highest in-vitro enzymatic degradability (521 g kg-1 DM), which even increased in a 40:60 mixture with maize. Lowest degradation was obtained with Flemingia macrophylla (248 g kg-1 DM), while the median of the forages approached 390 g kg-1 DM. It is concluded, that Vigna unguiculata herbage meal has the highest potential to be successfully included in pig diets, while Cratylia argentea meal should equally be assessed in vivo.